(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sahami FM, Habibie SA. 2021. Diversity of species in making up Nike fish schools and a new record of Eleotris melanosoma in Tomini Paguyaman Bay, Gorontalo, Indonesia. Biodiversitas 22: 5459-5467. Several estuaries in the waters of Tomini Bay are reported as the primary location for Nike fishing in Gorontalo; one of which is Paguyaman Bay. However, scientific information on Nike fish in the Tomini Bay waters is currently limited in Gorontalo Bay. The present study aims to determine the diversity of species in making up the Nike fish schools in Paguyaman Bay and show the types of constituent species whose distribution in Gorontalo waters has never been reported. A total of 1773 samples of Nike fish were collected from the sea to the estuary of Paguyaman Bay in one period of their emergence on April 8-10, 2021. The species were grouped based on the melanophore pattern’s similarity and then analyzed morphometrically. The molecular identification of COI mitochondrial DNA was performed on species with different morphological appearances from those found in Gorontalo Bay. The Discriminant Function Analysis (DFA) indicated that the main distinguishing character of morphometrics is body depth. The morphological results suggested that the Nike fish schools in Paguyaman Bay consisted of seven species, four genera, and two families, i.e., Sicyopterus longifilis, S. parvei, S. cynocephalus, Stiphodon semoni, Belobranchus segura, B. belobranchus, and Eleotris melanosoma. The first finding of E. melanosoma as a species making up the Nike fish schools in Paguyaman Bay was a new variant of the distribution of this species in Gorontalo waters and confirmed using morphology and molecular analysis. Further, based on the species composition, Nike fish schools in the waters of Paguyaman Bay show a typical species dominance trend during the recruitment process returning to freshwater, i.e., S. longifilis (52%) on the first day, Belobranchus segura (63.27%) on the second day, and Stiphodon semoni (83.43%) on the third day.